Density-transition based electron injector for laser driven wakefield accelerators - K. Schmid; A. Buck; C. M. S. Sears; J. M. Mikhailova; R. Tautz; D. Herrmann; M. Geissler; F. Krausz; L. Veisz (Physical Review Special Topics. Accelerators and Beams, 2010)
We demonstrate a laser wakefield accelerator with a novel electron injection scheme resulting in enhanced stability, reproducibility, and ease of use. In order to inject electrons into the accelerating phase of the plasma wave, a sharp downward density transition is employed. Prior to ionization by the laser pulse this transition is formed by a shock front induced by a knife edge inserted into a supersonic gas jet. With laser pulses of 8 fs duration and with only 65 mJ energy on target, the accelerator produces a monoenergetic electron beam with tunable energy between 15 and 25 MeV and on average 3.3 pC charge per electron bunch. The shock-front injector is a simple and powerful new tool to enhance the reproducibility of laser-driven electron accelerators, is easily adapted to different laser parameters, and should therefore allow scaling to the energy range of several hundred MeV.